Improving Peat Water Quality Using a Multi-stage Shell Sand, CTO, and Reverse Osmosis System in Sengkubang Village, Indonesia - Norita, Norita; Selviana, Selviana; Suwarni, Linda (Reflection Journal, 2025)
In many Indonesian peatland regions, communities still rely on peat water for drinking despite its very low pH, dark colour, and elevated loads of natural organic matter and dissolved metals. This study evaluates the performance of a small-scale, multi-stage treatment system that combines shell sand, CTO carbon block filtration, and reverse osmosis (RO) to improve peat water quality in Sengkubang Village with reference to Indonesian Regulation Permenkes No. 32/2017. A quasi experimental one group pretest–posttest design was applied, measuring total dissolved solids (TDS), turbidity, colour, odour, pH, iron (Fe) and manganese (Mn) in raw and treated water. The system substantially reduced turbidity and colour, with both parameters decreasing by more than 90 percent, and lowered TDS while keeping it well below the national limit. The pH shifted from strongly acidic to near neutral, and Fe was reduced to a small fraction of its initial concentration, far below both national and WHO oriented guideline values, whereas Mn remained safely below its standard. After treatment, all monitored parameters complied with Permenkes 32/2017. The results indicate that locally sourced shell sand can function as an effective pretreatment for RO in humic rich, acidic peat water when combined with CTO adsorption. Nevertheless, the findings are based on a single site and short observation period and do not include microbiological indicators, so the system should be regarded as a promising but still preliminary option that requires further seasonal, long term, and microbiological assessment.